Incidence and survival rates for adult malignant neuro-epithelial brain tumors in the Somme county (France): A retrospective, population-based study from 2003 to 2013. (March 2018) - Bello Roufai, D.; Caillet, P.; Lapôtre-Ledoux, B.; Trecherel, E.; Bauchet, L.; Chauffert, B.; Ganry, O.
Highlights: Overall incidence of brain neuroepithelial tumours increases with age and men have a significantly higher risk to develop these diseases. The increased age-adjusted incidence of neuroepithelial brain tumours from 2003 to 2013 that translates into an annual increase of 7.6%. Overall survival of neuroepithelial brain tumours significantly improved between 2003 and 2013. Abstract: Aims: To describe the incidence and survival rates for neuro-epithelial primary brain tumors (NPBTs) in adults in the Somme county between 2003 and 2013. Methods: By analyzing the Somme Cancer Registry, we calculated the age-standardized incidence rates (ASRs) for NPBTs. Independent effects of age, gender and period of diagnosis on the incidence were evaluated in a Poisson regression analysis. A Cox proportional hazards model was used to adjust the overall survival rates for age, gender, histologic group and period. Results: Of the 257 registered NPBTs, 193 (75.1%) were astrocytic tumors. The subpopulations most affected by NPBTs were men (incidence rate ratio (IRR) [95% confidence interval (CI)] females/males = 0.7 [0.55–0.90], p < 0.001) and the elderly (IRR [95% CI] = 1.02 [1.01–1.03] per year increment, p < 0.001). The ASR [95% CI] was 4.5 [3.9–5.1] cases per 100, 000 person-years. The increase in incidence [95%CI] between 2003 and 2013 was estimated to be 7.6% [3.4–11.2%] per year (p < 0.001). Survival improved significantly between the 2003–2008 period and the 2009–2013 period (hazard ratio [95%CI] = 0.70 [0.50–0.96], p = 0.03). Conclusion: We observed an increase in the incidence of NPBTs and in survival rates between 2009 and 2013. These increases might have been due to broader, earlier access to diagnostic tools and/or improvements in treatment procedures.